Pengendalian Sampah Di Tukad Mati Melalui Pengelolaan Sampah Dari Hulunya Menuju Desa Wisata - I Gusti Bagus Suryawan; I Made Jaya Senastri; I Nyoman Sutama (Postgraduated Community Service Journal, 2021)
Philosophically, the river is the source of life, is the lifeblood of the earth, therefore the water flowing in the river must be kept pure and clean. The Tukad Mati River stretches from north to south in the middle of the village of Padangsambian Kaja, so that its position is squeezed between settlements and residents' housing, therefore the cleanliness of the water in Tukad Mati is strongly influenced by waste management from residential and residential areas. To help realize and maintain the cleanliness of the dead body, the team, with the permission of the Community Service Institute, UNWAR collaborated with partners (Padangsambian Kaja Village) through a community partnership program with outreach activities and location planning to build public awareness that rivers are not a dumping ground for all kinds of waste, for that it is necessary carried out: sorting waste from households to reduce waste to rivers, forming a community that cares about rivers and waste banks, doing mutual cooperation on a regular basis, carrying out supervision by related parties so that the rules run effectively, structuring the dead river so that it can be used as a tourist spot and fishing place.